Innovation in libraries and information services - Baker, David, 1952-; Evans, Wendy, 1968- (Advances in library administration and organization,, 2016)
This volume of Advances in Library Administration and Organization takes as its underpinning theme the whole subject of innovation in Library and Information Services. It considers the various types of innovation through case studies and exemplars both from within the LIS sector and other cognate industries and environments. It will look at both the last and the next thirty years by charting major technology developments and the ways in which they have not only been adopted and adapted by library services but also how the resulting improvements and enhancements have impacted upon key user communities. But more importantly, the volume projects these developments forward and in addition forecasts and analyses likely future inventions and innovations and how LIS leaders and managers should not only respond but actually help to create and shape our future world.Written and edited by Professor David Baker and Wendy Evans, the volume will include contributions from: Dr Chris Batt; Dr Masanori Koizumi; Dr Tibor Koltay; Professor Derek Law; Dr Mike McGrath; Dr Bruce Massis; Chloe Mills; John Robinson; Dr Lara Skelly; Professor Jo Smedley; Dr Evgenia Vassilakaki; Dr Graham Walton.